Factors Influencing Syariah Mutual Fund Investment Decisions in Indonesia: What is FoMO's Role? (IQTISHADIA, 2025)
This research sought to investigate how fear of missing out (FoMO) among Indonesia's Generation Z mediated the effects of herding behavior, loss aversion, and financial literacy on the decision-making process for sharia mutual fund investments. This study employs a quantitative methodology. A questionnaire on a Likert scale from 1 to 10 was used to gather data, which was distributed to sharia mutual fund investors in Indonesia via Google Forms. Non-probability sampling was employed in the sample procedure. The study involved a sample of 150 respondents. The data analysis was conducted using the partial least squares-structural equation modeling (PLS-SEM) technique with the assistance of SmartPLS 3.0 software. The first test is the assessment of the measurement model. The second test is the evaluation of the inner model using the bootstrapping technique of 5000 samples. The study's findings revealed that herding behavior, loss aversion, and financial literacy significantly and positively influence investment decisions. FoMO was found to have no impact on investor decision-making. Additionally, the independent variable showed no significant influence on sharia mutual fund investment decisions when mediated by the FoMO variable.